Controller Design of Industrial Cooperative Robots - Urrea-Onate, E; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper deals with the design of control laws to industrial cooperative robotics. The main goal is to design and compare the behavior of different control structure in order to get an effective coordination of two manipulators. It is assumed that both manipulators have the same dynamical and a master slave strategy is used. For both master and slave manipulators, a combinations of PID and fuzzy PD control strategy are proposed. A numerical simulation is presented in order to compare the proposed controllers. © 2015 IEEE.